On the effectiveness of the work of private and public bailiffs in the forced execution of court decisions: a comparative analysis - Rusetska, O. O. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The article is devoted to a comprehensive study of the issue of the effectiveness of the introduction of the institute of private bailiffs and a comparative analysis of the work of state and private bailiffs in the implementation of compulsory enforcement of decisions. Based on the analysis of current legislation, it was established that state and private bailiffs have different legal status. A private bailiff, unlike a state bailiff, does not have the status of a civil servant, is a subject of independent professional activity, in addition, the legislator provides for different requirements for their position. It was established that the legislator provides for more requirements for the position of a private bailiff than for a state bailiff, this applies to age, education, work experience, etc. The system of enforcement proceedings is considered and different points of view of scientists on the effective model of compulsory enforcement of court decisions in our country are established, the views are divided into two groups, namely: a mixed form of compulsory enforcement of decisions (the existence of a state and private institute of compulsory enforcement), but a discussion arises regarding the powers of a private and state bailiff; the institute of private enforcement (scientists note the expediency of abolishing enforcement by state bailiffs). Particular attention is paid to the factors that determine the effectiveness of enforcement of court decisions by state and private bailiffs. Based on the analysis of the work of state and private bailiffs, it was found that the activities of private bailiffs in terms of enforcement of decisions are more effective than the activities of state bailiffs. This conclusion was supported by statistical data on the work of state and private bailiffs, in particular, the article provides an example that in 2024, on average, one private bailiff returned six times more money to creditors than one state bailiff. In addition, it is necessary to note the low level of enforcement of decisions by state bailiffs, which is associated with various factors. Also, attention is drawn to the need to initially equalize the powers of private and state bailiffs, granting them equal powers in terms of enforcement of decisions, and then gradually resolve the issue of adopting an appropriate model of enforcement that will be more effective for our state.